Almost Ready (Raton Range Raton, NM, 1984)
This article is about the new Cimarron gymnasium-cafetorium about to be complete and the school are slated to return to normal.
Newspaper article + photograph of the new Cimarron gymnasium-cafetorium.
Mater List Item # 23
File location is in the New Mexico File Cabinets
Keywords: Coker, Thelma -- Superintendent; Cimarron Schools; New Gyms; New Cafeterias; Bond Issues; School Projects; Cimarron, New Mexico